Effects of soil water deficits at different periods of growth on potato ( Solanum tuberosum) yield - Scaloppi, Edmar José (Pesquisa Agropecuaria Brasileira, 2014)
The effect on potato yield by soil water deficits at different times during plant growth. It was established in work conducted at Botucatu, São Paulo, Brazil, that potato (Solanum tuberasum L.) yield was related to intensity and duration of soil water deficit and stage of plant growth. Tuber yield was markedly influenced by soil water regime during the stage of tuberization and tuber development. Moderate water deficit (-1 bar soil water matric potential) at the initial growth stage or after vegetative growth did not affect potato yield. At any soil water regime a sequence of water deficits at all growth stages enhanced the damage when comparing with the effects observed at only one stage. Differences in yield between treatments, were based on the quantity of well-developed tubers found since the number of tubers was not significantly affected.